Mineral levels in lactating Lagos women: blood-breast milk correlation and environmental-nutritional influences - Oyelowo, Oluwakemi; Makwe, Christian; Adejare, Abdullahi; Ajulo, Oyinkansola; Dieobi, Cynthia (Universa Medicina, 2025)
Background Lifestyle choices and environmental exposure to certain materials have been reported to alter the distribution of key electrolytes in the blood and breastmilk of pregnant women and, in some cases, worsen micronutrient deficiencies. This study aimed to determine the association of sodium, iron, potassium, and calcium ions in maternal blood with those in breast milk and how maternal lifestyle routines could affect the level of these micronutrients.   Methods A cross-sectional study was conducted involving 30 breastfeeding mothers with newborns. They were administered a pre-tested questionnaire following informed consent. Blood and breastmilk specimens were obtained thereafter to determine the serum and breastmilk levels of iron, potassium, sodium, and calcium. Data were analyzed using unpaired t-tests with the significance level of p<0.05.   Results A significant reduction in serum and breastmilk potassium ion levels (p<0.001 for both) was found in lactating women taking vitamin D, vitamin B, calcium, and folic acid supplements, particularly with increased serum iron levels. Conversely, exposure to paints (p<0.001), radiation (p<0.001), borehole water (p<0.05) and tap water (p<0.05) increased potassium ion levels in both blood and breastmilk. Notably, significant correlations existed between blood and breastmilk levels of sodium and potassium ions.   Conclusions While breastmilk sodium and potassium ion levels are directly related to the level in the serum, supplemental intake of some vitamins as well as exposure to paints and radiation could significantly reduce blood and breastmilk potassium, thus further worsening the micronutrient deficiency (aka hidden hunger) in pregnant women.